Theoretical Basis and Implementation of the Idea of Sustainable Development in Forestry - Paschalis-Jakubowicz, Piotr (Problemy Ekorozwoju, 2011)
Use of the forest is the oldest form of human activity and also occurs if it takes place without the physical presence of man in the woods, becoming destructive action – intentional or unintentional, or creative activity – identifying and implementing specific needs. Use of forest functions such as: cultural, moral, ethical, religious, and many others, is not always quantifiable, and their direct measurement and evaluation, can be very difficult. This is due to both lack of appropriate economic tools and methods for the direct environmental analysis, as well as an inability to identify the various functions played by forests. The article is discussing the history of sustainable development in forestry, which opens with the law signed in 1364 by Philip VI of France, ordering that owners of the forest must take care of it. The next great theorists and practitioners of Forestry (Carlovitz, Cotta, Hundeshagen, Heyer), develop the concept, building a cohesive, well thought-structures of proceedings in the context of preserving stability, continuity and uniformity forest use. The real problem in implementation of the concept of sustainable forestry and forest multifunctionality, is unsolvable difficulty in anticipating the expectations of future generations as to the condition, appearance and composition of future forests. should be noted that promises benefits of the terms used in sustainable forest management (SFM), in relation to the multifunctional forestry cannot be met simultaneously and immediately. In forestry practice, all the forest functions, can be met only in a very long time horizon – calculated life expectancy of trees and stands. The search for solutions in this area should include not only areas of the modern, current knowledge, both the forest and in other branches of science, but also traditional knowledge. This would mean, that traditional knowledge, significantly important for the practice of forestry, can be the basis for the understanding of the multifunctionality of the forest in the context of sustainable development.